Challenges of financialised firm behaviour for Capital Markets Union. (3rd July 2015) - Ertürk, Ismail
Abstract : Capital Markets Union is a late but right project towards a truly single currency economic zone in the EU. However the CMU Green Paper chooses the wrong benchmark of US capital markets and is not based on evidence. The hegemonic corporate governance ideology of shareholder value maximisation that determines the financialised firm behaviour in the US has produced, since the 1980s, malign macroeconomic outcomes resulting in lower private investments, lower wages, regular stock market crises and socially and economically costly misalignment of the interests of owners and controllers of capital. The financialisation literature has amply examined these processes and recently international institutions like the OECD and the Bank for International Settlement have confirmed the findings of the financialisation literature with their own empirical evidence. Therefore the CMU project needs to be based on a better foundation of corporate governance that encourages long-term investments and true alignment of all stakeholders' and managers' interests.